Improvement in Back and Leg Pain and Disability Following Adult Spinal Deformity Surgery: Study of 324 Patients With 2-year Follow-up and the Impact of Surgery on Patient-reported Outcomes. Issue 4 (15th February 2019) - Verma, Ravi; Lafage, Renaud; Scheer, Justin; Smith, Justin; Passias, Peter; Hostin, Richard; Ames, Christopher; Mundis, Gregory; Burton, Douglas; Kim, Han Jo; Bess, Shay; Klineberg, Eric; et al.
Abstract : Study Design: A retrospective review of a prospective, multicenter adult spinal deformity (ASD) database. Objective: Our objective was to quantify the change in disability reported for patients with radiculopathy as compared with patients with back pain only following ASD realignment surgery. Summary of Background Data: Studies utilizing patient-reported outcomes (PROs) have shown that ASD patients suffer from significant pain and disability. Although surgical correction has been effective at improving back and leg pain, no studies have investigated the impact of radiculopathy on pain and disability in ASD patients. Methods: Inclusion criteria were age ≥ 18 years and presence of spinal deformity as defined by coronal Cobb angle ≥ 20°, sagittal vertical axis (SVA) ≥ 5 cm, pelvic tilt (PT) angle ≥ 25°, or thoracic kyphosis (TK) angle ≥ 60°. Demographics and PRO were collected. Patients with radiculopathy were propensity matched with patients with back pain. Preoperative, postoperative, and 2-year follow-up radiographic parameters and PRO were analyzed. Results: Three hundred twenty-four patients met inclusion criteria, and following propensity matching, 90 patients were placed into the radiculopathy and back pain groups. These groups showed no difference in demographic or radiographic parameters. The groups were similar in PRO, with a difference in leg pain as per design. At baseline, leg pain patients had higher disability [Oswestry Disability Index (ODI) and Scoliosis Research Society (SRS)]. Surgical strategies between the two groups showed no differences. Postoperative radiographic parameters showed no difference. Despite a significantly greater decrease in numerical rating scale (NRS) Leg for the leg pain group, postoperatively, these patients remained more disabled than the nonleg group in terms of NRS (back and leg), ODI, and most of the SRS domains. Conclusion: ASD patients with radiculopathy exhibit increased pain and disability when compared with patients without leg pain. This increased pain and disability persists after surgical correction in these patients. Level of Evidence: 3 Abstract : Adult spinal deformity patients exhibit pain and disability, however the impact of radiculopathy has not been studied. This study examines propensity matched groups of ASD patients with and without radiculopathy at baseline, postoperative, and 2 year follow up. Patients with radiculopathy have greater pain and disability and this persists postoperatively.